Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s10548-020-00795-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Attention for a Prolonged Duration Affects Dynamic Organizations of Frequency-Specific Functional Connectivity

Abstract: Sustained attention encompasses a cascade of fundamental functions. The human ability to implement a sustained attention task is supported by brain networks that dynamically formed and dissolved through oscillatory synchronization. The decrement of vigilance induced by prolonged task engagement affects sustained attention. However, little is known about which stage or combinations are affected by vigilance decrement. Here, we applied an analysis framework composed of weighted phase lag index (wPLI) and tensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Our results showed that dynamical complexity measures were related to the changing process of response, e.g., dynamical complexity measure MFEI (r = −0.35, p < 0.001) were significantly correlated to the task performance during sustained attention task. Previous studies also demonstrated that attention dynamically modulates brain rhythms (Liu et al, 2020;McCusker et al, 2020;Pagnotta et al, 2020). McCusker et al (2020) observed multi-spectral oscillatory robust effected by attention dynamically for both the directed and divided attention experiments in a MEG study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our results showed that dynamical complexity measures were related to the changing process of response, e.g., dynamical complexity measure MFEI (r = −0.35, p < 0.001) were significantly correlated to the task performance during sustained attention task. Previous studies also demonstrated that attention dynamically modulates brain rhythms (Liu et al, 2020;McCusker et al, 2020;Pagnotta et al, 2020). McCusker et al (2020) observed multi-spectral oscillatory robust effected by attention dynamically for both the directed and divided attention experiments in a MEG study.…”
Section: Discussionmentioning
confidence: 83%
“…McCusker et al (2020) observed multi-spectral oscillatory robust effected by attention dynamically for both the directed and divided attention experiments in a MEG study. Liu et al (2020) applied an complex analysis framework composed of weighted phase lag index and tensor component analysis and they found dynamic organizations of frequency-specific function connectivity can track the decrement and motivation of attention in sustained task. In a simplified perspective, dynamical complexity analysis conducted in this study may offer additional predictive value for attention.…”
Section: Discussionmentioning
confidence: 99%
“…We thus consider the tensor decomposition (or tensor component analysis) based methods for such dynamic community detection [18], [31], [34], [35], [36], [37] since the tensor decomposition enables multi-timescale dimensionality reduction both within and across temporal evolution for multiple subjects in a purely data-driven method. Tensor decomposition has recently been regarded as an extension of PCA for dynamic brain network analysis across subjects, where time-frequency vectorized adjacency matrices were formed into a tensor and decomposed into components characterizing brain network patterns with spectral-temporal features [9], [38], [39], [40] or temporal features [41], [42]. However, in this case, the topological organization of brain networks is unable to be directly revealed in the resulting components.…”
Section: Introductionmentioning
confidence: 99%